Residential intensification through a new statutory plan in Auckland: outcome evaluation and stakeholders' experience. Issue 5 (20th October 2022) - Liu, Wen; Beattie, Lee; Haarhoff, Errol
ABSTRACT: Conformance between plans and expected plan outcomes is at the heart of urban planning processes. Integrating an empirical evaluation and stakeholders' experience of the realisation of intended intensification goals, this article presents the contradictions between the plan instruments and the anticipated plan outcomes to enable higher intensification than the superseded plans. The findings suggest that statutory land use planning should be accompanied by a thorough outcome-based evaluation and a review of conflicting planning tasks and purposes. The article concludes with recommendations for planning monitoring and strengthening the statutory plan to achieve its expectations.